1997
DOI: 10.1002/etc.5620160428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acclimation period on the relationship of acute copper toxicity to water hardness for fathead minnows

Abstract: Abstract-The acute (96-h) toxicity of copper sulfate to fathead minnows was tested in a 2 ϫ 2 factorial experiment, with factors being low (ca. 1 meq/L) and high (ca. 4 meq/L) water hardness during an acclimation period and low and high hardness during the exposure period. Acclimation hardness was found to have no significant effects on copper lethality, except that the 24-h LC50 at high exposure hardness was 44% higher for fish subject to low acclimation hardness than fish subject to high acclimation hardness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Barron and Albeke [17] reported a similar response with zinc, where acclimation to high‐hardness (348 mg/L as CaCO 3 ) waters reduced zinc uptake by RBT compared to those cultured at a lower hardness (43 mg/L as CaCO 3 ). In studies with fathead minnows, Erickson et al [5] reported no significant differences in 96‐h LC50s due to acclimation conditions, although LC50s were slightly higher for organisms acclimated in the higher‐hardness water (215 vs 47 mg/L hardness as CaCO 3 ). On the other hand, studies by Welsh et al [10] showed that RBT were more tolerant to copper in hard water (hardness of 180 mg/L as CaCO 3 ) when they were acclimated for two weeks in softer waters (88 mg/L as CaCO 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Barron and Albeke [17] reported a similar response with zinc, where acclimation to high‐hardness (348 mg/L as CaCO 3 ) waters reduced zinc uptake by RBT compared to those cultured at a lower hardness (43 mg/L as CaCO 3 ). In studies with fathead minnows, Erickson et al [5] reported no significant differences in 96‐h LC50s due to acclimation conditions, although LC50s were slightly higher for organisms acclimated in the higher‐hardness water (215 vs 47 mg/L hardness as CaCO 3 ). On the other hand, studies by Welsh et al [10] showed that RBT were more tolerant to copper in hard water (hardness of 180 mg/L as CaCO 3 ) when they were acclimated for two weeks in softer waters (88 mg/L as CaCO 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many water quality parameters have been shown to affect copper toxicity to aquatic organisms, including water hardness, alkalinity, sodium, pH, and dissolved organic carbon [1–4]. Of these factors, the water hardness in which organisms were exposed is one of the more important factors affecting sensitivity to copper [2,5,6]. Not only will the total hardness of a water influence copper toxicity, but the relative ratio of the individual ions that make up hardness (Ca 2+ and Mg 2+ ) can also alter copper toxicity to some species [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation